Do patients bypass primary care for common health problems under a free-access system? Experience of Taiwan - Li-Lin Liang; Nicole Huang; Yi-Jung Shen; Annie Yu-An Chen; Yiing-Jenq Chou (BMC Health Services Research, 2020)
Abstract Background A common challenge for free-access systems is that people may bypass primary care and seek secondary care through self-referral. Taiwan’s government has undertaken various initiatives to mitigate bypass; however, little is known about whether the bypass trend has decreased over time. This study examined the extent to which patients bypass primary care for treatment of common diseases and factors associated with bypass under Taiwan’s free-access system. Methods This repeated cross-sectional study analyzed data from Taiwan’s National Health Insurance Research Database. A random sample of 1 million enrollees was drawn repeatedly from the insured population during 2000–2017. To capture visits beyond the community level, the bypass rate was defined as the proportion of self-referred visits to the top two levels of providers, namely academic medical centers and regional hospitals, among all visits to all providers. Subgroup analyses were conducted for visits with a single diagnosis. Logistic regressions were used to investigate factors associated with bypass. Results The standardized bypass rate for all diseases analyzed exhibited a decreasing trend. In 2017, it was low for common cold (0.7–1.3%), moderate for hypertension (14.0–29.5%), but still high for diabetes (32.0–47.0%). Moreover, the likelihood of bypass was higher for male, patients with higher salaries or comorbidities, and in areas with more physicians practicing in large hospitals or less physicians working in primary care facilities. Conclusions Although the bypass trend has decreased over time, continuing efforts may be required to reduce bypass associated with chronic diseases. Both patient sociodemographic and market characteristics were associated with the likelihood of bypass. These results may help policymakers to develop strategies to mitigate bypass.